MSG - DEMON IN FOOD - CHATTERJEE, BANDANA; PATEL, TINKAL (International Journal of Clinical and Biomedical Research, 2016)
Flavor enhancers are used to bring out the flavor in a wide range of foods without adding a flavor of their own. Any food product that can be added to food to enhance its taste especially to make it taste more savoury or to add more Umami flavor. Umani taste that is found also in Glutamate. The anti MSG forces counter such information by stating that naturally occuring glutamate is different than added Glutamate is different than added glutamate. Research has demonstrated, However that the two are indeed metabolized identically.